Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm trying to compute: $$\int_{0}^{1}\frac{x^4+1}{x^6+1}dx.$$

I tried to change $x^4$ into $t^2$ or $t$, but it didn't work for me.

Any suggestions?


share|cite|improve this question
$\mathrm{d}x$ went missing! – user21436 Jan 21 '12 at 17:58
W.A. says that you should use partial fractions... – pedja Jan 21 '12 at 18:00
W.A. says it is $\pi/3$. – Jon Jan 21 '12 at 18:16
I'm trying to find a way for computing it easily without using W.A... – Jozef Jan 21 '12 at 18:22
up vote 28 down vote accepted

Edited Here is a much simpler version of the previous answer.

$$\int_0^1 \frac{x^4+1}{x^6+1}dx =\int_0^1 \frac{x^4-x^2+1}{x^6+1}dx+ \int_0^1 \frac{x^2}{x^6+1}dx$$

After canceling the first fraction, and subbing $y=x^3$ in the second we get:

$$\int_0^1 \frac{x^4+1}{x^6+1}dx =\int_0^1 \frac{1}{x^2+1}dx+ \frac{1}{3}\int_0^1 \frac{1}{y^2+1}dy = \frac{\pi}{4}+\frac{\pi}{12}=\frac{\pi}{3} \,.$$

P.S. Thanks to Zarrax for pointing the stupid mistakes I did...

share|cite|improve this answer
The integrand actually doesn't change under your substitution, check your work. Also, the range ends out going from 1 to $\infty$ after the substitution. – Zarrax Jan 21 '12 at 22:18
Your correction is also incorrect, as you are now subtracting $x^2$ twice from the numerator... change one of the $x^2$'s to a $-x^2$ and it should work. – Zarrax Jan 21 '12 at 22:22
Edited, actually there was no need for the substitution... The previous answer was waaay more complicated than it needed :) – N. S. Jan 21 '12 at 22:23
+1 Very clever! – Américo Tavares Jan 21 '12 at 23:17
This answer, now, should be the accepted one (+1). – John Bentin Jan 22 '12 at 15:10

The denominator of the integrand $f(x):=\dfrac{x^{4}+1}{x^{6}+1}$ may be factored as \begin{eqnarray*} x^{6}+1 &=&\left( x^{2}+1\right) \left( x^{4}-x^{2}+1\right) \ &=&\left( x^{2}+1\right) \left( x^{2}-\sqrt{3}x+1\right) \left( x^{2}+\sqrt{3 }x+1\right) \end{eqnarray*}

If you expand $f(x)$ you get

$$\begin{eqnarray*} f(x) &=&\frac{2}{3}\frac{1}{x^{2}+1}+\frac{1}{6}\frac{1}{x^{2}-\sqrt{3}x+1}+ \frac{1}{6}\frac{1}{x^{2}+\sqrt{3}x+1} \\ &=&\frac{2}{3}\frac{1}{x^{2}+1}+\frac{2}{3}\frac{1}{\left( 2x-\sqrt{3} \right) ^{2}+1}+\frac{2}{3}\frac{1}{\left( 2x+\sqrt{3}\right) ^{2}+1}. \end{eqnarray*}$$

Since $$ \int \frac{1}{x^{2}+1}dx=\arctan x $$ and $$ \begin{eqnarray*} \int \frac{1}{\left( ax+b\right) ^{2}+1}dx &=&\int \frac{1}{a\left( u^{2}+1\right) }\,du=\frac{1}{a}\arctan u \\ &=&\frac{1}{a}\arctan \left( ax+b\right), \end{eqnarray*} $$ we have $$ \begin{eqnarray*} \int_{0}^{1}\frac{x^{4}+1}{x^{6}+1}dx &=&\frac{2}{3}\int_{0}^{1}\frac{1}{% x^{2}+1}dx+\frac{2}{3}\int_{0}^{1}\frac{1}{\left( 2x-\sqrt{3}\right) ^{2}+1}% dx \\ &&+\frac{2}{3}\int_{0}^{1}\frac{1}{\left( 2x+\sqrt{3}\right) ^{2}+1}dx \\ &=&\frac{2}{3}\arctan 1+\frac{2}{3}\left( \frac{1}{2}\arctan \left( 2-\sqrt{3% }\right) -\frac{1}{2}\arctan \left( -\sqrt{3}\right) \right) \\ &&+\frac{2}{3}\left( \frac{1}{2}\arctan \left( 2+\sqrt{3}\right) -\frac{1}{2}% \arctan \left( \sqrt{3}\right) \right) \\ &=&\frac{1}{6}\pi +\frac{1}{3}\left( \arctan \left( 2-\sqrt{3}\right) +\arctan \left( \sqrt{3}\right) \right) \\ &&+\frac{1}{3}\left( \arctan \left( 2+\sqrt{3}\right) -\arctan \left( \sqrt{3% }\right) \right) \\ &=&\frac{1}{6}\pi +\frac{1}{3}\left( \arctan \left( 2-\sqrt{3}\right) +\arctan \left( 2+\sqrt{3}\right) \right) \\ &=&\frac{1}{6}\pi +\frac{1}{6}\pi \\ &=&\frac{1}{3}\pi, \end{eqnarray*} $$

because$^1$ $$ \arctan \left( 2-\sqrt{3}\right) +\arctan \left( 2+\sqrt{3}\right) =\frac{1}{ 2}\pi. $$

$^1$We apply the arctangent additional formula to $u=2-\sqrt{3}$ and $v=2+\sqrt{3}$

$$ \arctan u+\arctan v=\arctan \frac{u+v}{1-uv}. $$ Since the product $uv=1$ and $\arctan \left( 2-\sqrt{3}\right) >0,\arctan \left( 2+\sqrt{3}\right) >0$, we get on the right $\arctan \dfrac{4}{1-1}= \dfrac{\pi }{2}.$

share|cite|improve this answer

A not so simple but funny way to compute it :

Denote I the value we are looking for. With a power series expansion of the integrand, we have $$ I = 1 + 2\sum_{n=1}^\infty \frac{(-1)^n}{36n^2-1} $$ With another series expansion and interversion of the summation, we have $$ I = 1 + 2\sum_{k=1}^\infty 6^{-2k}\sum_{n=1}^\infty \frac{(-1)^{n-1}}{n^{2k}} $$ We recognize the Dirichlet Eta function evaluated at even integers, so $$ I = 1+\sum_{k=1}^\infty \frac{(2^{2k}-2)\pi^{2k}}{6^{2k}}\frac{|B_{2k}|}{(2k)!} $$ Recognizing the well-known series exansion $$ 1 - \frac x2 \mathrm{cot} \frac x2 = \sum_{k=1}^\infty \frac{|B_{2k}| x^{2k}}{(2k)!},$$ we have $$ I = 1 + f(\pi / 3) - 2f(\pi/6), $$ where $f$ is the above function.

The trigonometric computation is not trivial but we eventually find $$ I = \frac{\pi}{3} $$

share|cite|improve this answer

First substitute $x=\tan\theta$. Simplify the integrand, noticing that $\sec^2\theta$ is a factor of the original denominator. Use the identity connecting $\tan^2\theta$ and $\cos2\theta$ to write the integrand in terms of $\cos^22\theta$. Now the substitution $t=\tan2\theta$ reduces the integral to a standard form, which proves $\pi/3$ to be the correct answer. This method seems rather roundabout in retrospect, but it requires only natural substitutions, standard trigonometric identities, and straightforward algebraic simplification.

share|cite|improve this answer

one way is partial fractions on $$ \frac{x^4+1}{x^6+1}=\frac{(x-e^{\pi i/4})(x-e^{3\pi i/4})(x-e^{5\pi i/4})(x-e^{7\pi i/4})}{(x-e^{\pi i/6})(x-e^{3\pi i/6})(x-e^{5\pi i/6})(x-e^{7\pi i/6})(x-e^{9\pi i/6})(x-e^{11\pi i/6})} $$ $$ =\frac{(x^2-\sqrt{2}x+1)(x^2+\sqrt{2}x+1)}{(x^2+1)(x^2+\sqrt{3}x+1)(x^2-\sqrt{3}x+1)} $$

share|cite|improve this answer

Note that $$I=\int_{0}^{1}\frac{x^4+1}{x^6+1}\,dx\quad\stackrel{\large x\,\mapsto\,\frac{1}{x}}\Longrightarrow\quad I=\int_{1}^{\infty}\frac{x^4+1}{x^6+1}\,dx\quad\Longrightarrow\quad I=\frac{1}{2}\int_{0}^{\infty}\frac{x^4+1}{x^6+1}\,dx$$ Using (proof can be seen here) $$\int_0^\infty\dfrac{x^{\large a-1}}{1+x^b}\ dx=\frac{\pi}{b}\csc\left(\frac{a\pi}{b}\right)$$ then $$I=\frac{1}{2}\int_{0}^{\infty}\frac{x^4+1}{x^6+1}\,dx=\frac{1}{2}\left[\frac{\pi}{6}\csc\left(\frac{5\pi}{6}\right)+\frac{\pi}{6}\csc\left(\frac{\pi}{6}\right)\right]=\frac{\pi}{3}$$

share|cite|improve this answer

$\newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert}$ \begin{align} &\color{#66f}{\large\int_{0}^{1}{x^{4} + 1 \over x^{6} + 1}\,\dd x} =\half\pars{\int_{0}^{1}{x^{4} + 1 \over x^{6} + 1}\,\dd x +\int_{0}^{1}{x^{4} + 1 \over x^{6} + 1}\,\dd x} \\[5mm]&=\half\bracks{\int_{0}^{1}{x^{4} + 1 \over x^{6} + 1}\,\dd x +\int_{\infty}^{1}{1/x^{4} + 1 \over 1/x^{6} + 1}\,\pars{-\,{\dd x \over x^{2}}}} \\[5mm]&=\half\pars{\int_{0}^{1}{x^{4} + 1 \over x^{6} + 1}\,\dd x +\int_{1}^{\infty}{x^{4} + 1 \over x^{6} + 1}\,\dd x} =\half\int_{0}^{\infty}{x^{4} + 1 \over x^{6} + 1}\,\dd x =\color{#66f}{\large% {1 \over 4}\int_{-\infty}^{\infty}{x^{4} + 1 \over x^{6} + 1}\,\dd x} \end{align}

Zeros of $\ds{\quad x^{6} + 1 = 0\quad}$ are given by $\ds{\quad x_{n} = \exp\pars{\bracks{2n + 1}\,{\pi \over 6}\,\ic}}$, $\ds{n = 0,1,2,\ldots,5}$, such that:

\begin{align} &\color{#66f}{\large\int_{0}^{1}{x^{4} + 1 \over x^{6} + 1}\,\dd x} ={1 \over 4}\sum_{n\ =\ 0}^{2}2\pi\ic\lim_{x\ \to\ x_{n}}\bracks{% \pars{x - x_{n}}\,{x^{4} + 1 \over x^{6} + 1}} ={\pi\ic \over 2}\sum_{n\ =\ 0}^{2}{x_{n}^{4} + 1 \over 6x_{n}^{5}} \\[5mm]&={\pi\ic \over 12} \sum_{n\ =\ 0}^{2}{x_{n}^{2} + x_{n}^{-2} \over x_{n}^{3}} ={\pi\ic \over 12}\sum_{n\ =\ 0}^{2} {2\,\Re\pars{x_{n}^{2}} \over \pars{-1}^{n}\,\ic} ={\pi \over 6}\,\Re\sum_{n\ =\ 0}^{2}\pars{-1}^{n}x_{n}^{2} \\[5mm]&={\pi \over 6}\,\Re\bracks{\exp\pars{{\pi \over 3}\,\ic} -\exp\pars{\pi\ic} + \exp\pars{{5\pi \over 3}\,\ic}} ={\pi \over 6}\bracks{\half -\pars{-1} + \half} =\color{#66f}{\large{\pi \over 3}} \end{align}

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.